The experience of teachers in the early years of elementary school contributing to the evaluation of the applicability of the prototype of a digital pedagogical game for the Teaching of probability (Revista Contexto & Educação, 2024)
The objective of this work was to analyze the digital game "Probability in Action" referring to the player's experience or its applicability during the interaction with the game. This evaluation was carried out in an extension course in which a questionnaire was applied to determine the impressions of teachers in the early years of Elementary School who teach mathematics according to the degree of satisfaction in relation to the player's experience. It was based on the MEEGA+ model in its seven subdimensions: challenge; satisfaction; social interaction; fun; focused attention; relevance; and perceived learning. The results showed positive aspects related to all dimensions, that is, that the game has attributes and provides dynamic, fun and competitive interaction among participants. Finally, despite suggestions for improving the digital game, teachers highlight the relevance of the game as it presents benefits as a teaching tool for teaching probability in the early years of Elementary School.
Keywords: Digital pedagogical game; Teaching Probability; Early Years of Elementary School; Player experience